Pocket PCs! : - Sherman, Erik B. (SYBEX, 2001)
Pocket PCs! I Didn’t Know You Could Do That...shows you not only how to track your business expenses but also how to expandyour Pocket PC into a digital camera or GPS device. Connect to your network,watch video, and play Pocket golf. Don't wasteanother minute... Turn your Pocket PC into a powerhouse Dream Machine for workand play! Make your Pocket PC an integral part of your life. With this book,you'll learn how to: Browse the Internet; Executecommon business applications; Read e-books; Listen to MP3 music files; Use Excel and Word .